2014
DOI: 10.1111/crj.12180
|View full text |Cite
|
Sign up to set email alerts
|

COPD phenotypes in a lung cancer screening population

Abstract: Combining LDCT with PFT and a comprehensive questionnaire allows subgroup classification of COPD phenotypes in a high-risk population and may lead to earlier intervention and an improved framework for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Twenty-five to thirty percent of participants were discordant for FEV 1 /FVC-defined COPD and one of the qCT measures. This type of distinction was also reported in a population of current and ex-smokers involved in a lung screening program, where 17% of subjects had obstruction based on FEV 1 /FVC and no evidence of emphysema based on radiologist evaluation of the CT, 15% had no FEV 1 /FVC-defined obstruction but had evidence of emphysema based on radiologist evaluation of the CT, and 27% had findings of both (25). …”
Section: Discussionsupporting
confidence: 53%
“…Twenty-five to thirty percent of participants were discordant for FEV 1 /FVC-defined COPD and one of the qCT measures. This type of distinction was also reported in a population of current and ex-smokers involved in a lung screening program, where 17% of subjects had obstruction based on FEV 1 /FVC and no evidence of emphysema based on radiologist evaluation of the CT, 15% had no FEV 1 /FVC-defined obstruction but had evidence of emphysema based on radiologist evaluation of the CT, and 27% had findings of both (25). …”
Section: Discussionsupporting
confidence: 53%
“…Although there is no validated score for daily clinical practice, the Bhalla score includes several elements that measure the extent and severity of bronchiectasis and other radiologic features associated with them [10].While other scales scarcely used in literature have some advantages in accuracy or good inter-observer variability, Bhalla score may show the severity of the disease more completely. The severity of bronchiectasis was significantly associated with age, smoking history, airflow limitation, lower FEV1, more frequent emphysema and coronary calcium, as previously seen in other studies [7,12,[28][29][30] Airflow limitation is quite common in patients with bronchiectasis [31][32][33] and was found in 55% of individuals with bronchiectasis in our cohort compared to 45% of the controls. In a study of 200 patients with bronchiectasis, airway obstruction was found in 43% and the presence and severity of airflow obstruction was proportional to the severity of bronchiectasis regardless of pack-years, sex or age [3].The finding of bronchiectasis in asymptomatic individuals, albeit mild in most instances, underlines the underdiagnosis of this condition.…”
Section: Burden Of Bronchiectasissupporting
confidence: 87%
“…Finally, since tumor nodules appear concave and mimic benign nodules when the surrounding parenchyma is emphysematous (23, 31, 32), as such, small pulmonary nodules likely have a greater probability of malignancy in the present of emphysema. This could be especially important since COPD phenotypes are highly prevalent in lung cancer screening populations (33). …”
Section: Discussionmentioning
confidence: 99%